The management and control of quality - Evans, James R. (Thomson South-western, 2005)
The market leader in quality management, this text is built on the strength and experience of well-known authors in the field. Experience as examiners for the Malcolm Baldrige Award, allow both Evans and Lindsay to integrate the framework and essential content of the Malcolm Baldrige National Quality Award criteria throughout the text. This edition continues to provide a managerially oriented, integrated view with a blend of pertinent technical topics. It contains revised, integrated, and more comprehensive coverage of Six Sigma philosophy, concepts, and techniques. New chapters on Principles of Six Sigma and Design for Six Sigma are included. The new edition also has coverage of most of the Body of Knowledge (BOK) required for ASQ certification as a Certified Quality Manager.